The empirical base of linguistics: Grammaticality judgments and linguistic methodology - T. Schütze, Carson (Classics in Linguistics, 2016)
Throughout much of the history of linguistics, grammaticality judgments - intuitions about the well-formedness of sentences - have constituted most of the empirical base against which theoretical hypothesis have been tested. Although such judgments often rest on subtle intuitions, there is no systematic methodology for eliciting them, and their apparent instability and unreliability have led many to conclude that they should be abandoned as a source of data.